Sistem Peminjaman Buku Pesan-Antar di Perpustakaan Kantor Perwakilan Bank Indonesia Provinsi Sumatera Barat - Olnasvi, Nadhea; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2016)
Based on the research results, we can conclude the following: First, the Library of Bank Indonesia Representative Office of West Sumatra province wore cyber library application system. Second, the obstacles encountered on the system design borrowing books home delivery, namely: (1) users (employees of Bank Indonesia) will be reluctant to come to the Library of the Representative Office of Bank Indonesia, (2) Library of the Representative Office of Bank Indonesia's West Sumatra province had to add librarians whose task is to deliver the book; (3) lower costs such as buying a vehicle that is useful for transporting the books borrowed users; and (4) limited collection in Perpustakaaan Bank Indonesia Representative Office of West Sumatra Province. Third, efforts are being made to overcome the obstacles, namely: (1) Library of Bank Indonesia Representative Office of West Sumatra province had to do many activities that still visited by the user; (2) seek professional librarians in delivering books; (3) sought costs as little as possible; (4) add to the collection at the Library of Bank Indonesia Representative Office of West Sumatra ProvinceKeyword:design, lending system, and library